A new living species of degu, genus Octodon (Hystricomorpha: Octodontidae) - D'Elía, Guillermo (2021)
We combine morphological (qualitative and quantitative data) and genetic (one mitochondrial and one nuclear gene) data from a large set of specimens of Octodon from the four currently recognized living species of the genus. The integration of the results (qualitative assessment, multivariate analysis of cranial measurements, and gene trees) allows us to state that 1) the current taxonomic scheme does not reflect the species diversity of Octodon; 2) in particular, as currently understood O. bridgesii likely is a complex of three species; 3) one of these, encompassing the southern populations of the genus, in the Araucanía Region (Chile) and Neuquén Province (Argentina), is named and described here as a new species; and 4) the mitochondrial gene tree departs from the nuclear gene tree with respect to O. pacificus and the new species here described.